2017
DOI: 10.3389/fneur.2017.00446
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of the Corpus Callosum in Epilepsy Patients with Secondarily Generalized Seizures

Abstract: The corpus callosum (CC) plays an important role in generalization of seizure activity. We used resting-state function magnetic resonance imaging (rs-fMRI) to investigate the regional and interregional functional connectivity of CC in patients with magnetic resonance imaging (MRI)-negative and secondarily generalized seizures. We measured the multi-regional coherences of blood oxygen level-dependent (BOLD) signals via rs-fMRI, cortical thickness via high-resolution T1-weighted MRI, and white matter (WM) integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(33 reference statements)
2
4
0
Order By: Relevance
“…In this context, several studies have shown that there are changes in the functional activity/connectivity in patients with these lesions, particularly in the DMN and RSNs (Peng & Hsin, 2017). We found, in accordance with those studies, that there is indeed a disruption of the DMN for this network as estimated by BP using the critical parameter of the normal HC (Fig.…”
Section: Predicting Rsns Of Pathological Networksupporting
confidence: 91%
See 1 more Smart Citation
“…In this context, several studies have shown that there are changes in the functional activity/connectivity in patients with these lesions, particularly in the DMN and RSNs (Peng & Hsin, 2017). We found, in accordance with those studies, that there is indeed a disruption of the DMN for this network as estimated by BP using the critical parameter of the normal HC (Fig.…”
Section: Predicting Rsns Of Pathological Networksupporting
confidence: 91%
“…Despite the obvious effect on the functional interaction of neuronal populations, the lesions of the CC usually lead to mechanical and other changes in the brain that are not necessarily related to functional activity, but can imply local impairments of the normal functional behavior of neuronal masses. In this context, several studies have shown that there are changes in the functional activity/connectivity in patients with these lesions, particularly in the DMN and RSNs (Peng & Hsin, 2017). We found, in accordance with those studies, that there is indeed a disruption of the DMN for this network as estimated by BP using the critical parameter of the normal HC (Fig.…”
Section: Predicting Rsns Of Pathological Networksupporting
confidence: 91%
“…eralization. 3,14 In some patients with generalized seizures, focal seizure onset might be discovered following disruption of the rapid propagation between two hemispheres after corpus callosotomy. 2 Therefore, the bilateral epileptic networks in generalized epilepsy with focal onset could have greater reliance on the corpus callosum for seizure propagation than the bilateral epileptic networks in generalized epilepsy with nonfocal bilateral synchronization.…”
mentioning
confidence: 99%
“…CC is a C-shaped white matter structure that connects the cerebral hemispheres and mediates information transfers between them [3]. Moreover, as a brain connector and coordinator, the CC has been strongly implicated in the pathogenesis of psychosis and in seizures of generalized, atonic, or unexplained natures (e.g., head trauma or alcohol withdrawal, instances with no obvious cause) [4,5]. It has been documented that, patients who experience multiple unprovoked focal and partial seizures, which could spread via the CC, may develop clinical epilepsy over time [5].…”
Section: Introductionmentioning
confidence: 99%